2023
DOI: 10.1002/wlb3.01071
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the accuracy of counting large ungulate species (red deer Cervus elaphus) with UAV‐mounted thermal infrared cameras during night flights

Abstract: Unmanned aerial vehicles (UAVs) are increasingly used in wildlife surveying, including estimation of population densities. It is essential that we evaluate and test new survey methods to guide optimal sampling strategies. This study aimed to assess the accuracy of using a UAV-mounted thermal infrared (TIR) camera to count red deer Cervus elaphus populations, and how this was influenced by flight season, height and velocity, in order to help guide future census design. We flew 57 flights across a captive popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Simplest, most cost effective, and likely most accurate, however, are simple counts from drone-based thermal videography, which in this study captured population density within a few hours of flights-with subsequent processing and analysis-and has been shown in studies of known captive animals to reproduce known population sizes with high fidelity [31,68,69]. Flights repeated seasonally could capture many of the spatiotemporal patterns revealed by long-term camera trapping and NMM analysis, and the spatial quality of aerial videography enables georeferenced observations of animal movement and short-term patterns of habitat use [32].…”
Section: Discussionmentioning
confidence: 99%
“…Simplest, most cost effective, and likely most accurate, however, are simple counts from drone-based thermal videography, which in this study captured population density within a few hours of flights-with subsequent processing and analysis-and has been shown in studies of known captive animals to reproduce known population sizes with high fidelity [31,68,69]. Flights repeated seasonally could capture many of the spatiotemporal patterns revealed by long-term camera trapping and NMM analysis, and the spatial quality of aerial videography enables georeferenced observations of animal movement and short-term patterns of habitat use [32].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that UAVs can be used effectively in wildlife surveys and that this technology can improve management actions. Similarly, a study by Zabel et al [16] evaluated the accuracy of UAVs and thermal infrared cameras in counting red deer populations. The study revealed that factors such as season, flight altitude and temperature affect the accuracy of the UAV.…”
Section: Drone Technology In Animal Health and Managementmentioning
confidence: 99%
“…The concerns raised by Duporge et al [13] emphasize the ethical use of UAV technology. However, research by Ezat et al [15] and Zabel et al [16] shows that UAVs have potential for accurate population counts and more effective monitoring of wildlife. Therefore, harmonization of regulatory frameworks and ethical guidelines for the use of UAVs in the future may lead to more widespread use of this technology in wildlife research.…”
Section: Drone Technology In Animal Health and Managementmentioning
confidence: 99%
“…For example, in winter, ungulates have thick winter coats that allow them to retain heat and survive harsh conditions and as such, less heat may be escaping the coat (Parker and Robbins 2018). A lack of heat emission has been previously observed in thermal imaging studies, where thermal cameras have a difficult time picking up certain species during certain temperature ranges (Kuhn & Meyer, 2009;Zabel et al, 2023). As a result, capture probability may be even lower during mid-winter months for some wildlife species.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%